IMPACT OF SHG ON RURAL WOMEN’S EXPENDITURE PATTERN ON FOOD, HEALTH AND HYGIENE DURING COVID-19 (International Journal of Food and Nutritional Sciences, 2022)
The study discusses how Self-Help Groups helped marginal Indian women to financially sustain during and after COVID-19. By offering options for revenue generation and support for daily living during the COVID-19 scenario, Self-Help Groups have played a significant role in empowering its members. The study pinpoints a potential mechanism by which COVID-19 circumstances has impacted on women's expenditure pattern on food, health, hygiene and other essential heads.Self-help groups have been crucial in empowering its members throughout the COVID-19 scenario by offering them opportunities for money generation and support for their way of life. The study identifies a potential mechanism by which COVID-19 circumstances may impact on women's financial decisions and spending nature on essential heads like food, health and hygiene. Self-Help Groups are an outstanding form of economic intermediation in India. The method syndicates access to low-cost financial services with a progression of self- management and growth for the women who are SHG member.The study has helped to understand how a SHGs activity has helped women to manage money for their daily activities during Covid-19 situation. A credit access from SHGs assisted women during and after Covid-19 to stand on their own feet and empowered themselves.